DESIGNING AN INSET COURSE FOR THE COLLEGE SUBJECT TEACHERS TO TEACH IN ENGLISH FOR INTERNATIONAL PROGRAMS - Dr. Suharno (Master Program in Linguistics, Diponegoro University, 2013)
In globalization era making a broader networking among universities is urgent. To realize such a cooperation several Indonesian universities are opening international programs but the common problem faced in higher education level is the lack of human resources who master English. To overcome the problem, some short courses were conducted to improve the college subject teachers’ English competence. Service English Unit (SEU), Diponegoro University is a language center carrying out such a training in cooperation with Univesitas Negeri Yogyakarta funded by Program Hibah Kompetensi Berbasis Institusi (PHKI) DIKTI Jakarta. The training lasting for 27 hours covered the components as follows: lecture preparation, academic language, grammar & phonetics, developing students’ learning and communication skills, course outline, project.Dalam era globalisasi membuat jaringan yang lebih luas antar universitas urgen. Untuk mewujutkan kerjasama semacam itu beberapa perguruan tinggi Indonesia membuka program internasional tetapi masalah umum yang dihadapi dalam tingkat perguruan tinggi adalah terbatasnya sumberdaya manusia yang menguasai bahasa Inggris. Untuk mengatasi masalah ini, beberapa kursus singkat diselenggarakan untuk meningkatkan kompetensi bahasa Inggris para pengajar matakuliah bidang studi. Service English Unit (SEU), Universitas Diponegoro merupakan pusat bahasa yang menyelenggarakan pelatihan semacam itu kerja sama dengan Universitas Negeri Yogyakarta (UNY) yang dibiayai oleh Program Hibah Kompetensi Berbasis Institusi (PHKI) DIKTI Jakarta. Pelatihan yang berlangsung 27 jam meliputi komponen sebagai berikut: persiapan kuliah, bahasa akademik, grammar & fonetik, pengembangan ketrampilan belajar dan komunikasi peserta, silabus, proyek.